Exposing the boundaries of safety: examining support for temporary migrants experiencing domestic and family violence - Segrave, Marie Therese (The borders of violence, 2024)
In this chapter, we explore how the border dictates the boundaries of safety for temporary migrants experiencing domestic and family violence (DFV). Our analysis of the structural limits of safety reveals the ways in which migration status impacts the responsiveness of various systems – police, DFV support services and other state systems – when temporary migrants seek help in the context of DFV. We highlight that while the rhetoric of support and protection dominates broad agendas and commitments to DFV at every level of government, what is evidenced in the chapter is that different systems operate according to different and often conflicting interpretations and understandings of women's safety. Our analysis highlights the limits on access to safety for victim-survivors and the consequences for temporary migrants who seek safety and DFV support. Specifically, we explore the harms women experience when systems are unresponsive and/or are limited in scope owing to the administration of migration status and the migration system. We identify how this works to sustain violence against women, particularly where migration status is prioritised over safety from DFV.